Biological monitoring of cyclophosphamide and ifosfamide in urine of hospital personnel occupationally exposed to cytostatic drugs. - Ensslin, A S (1994)
The occupational exposure of 21 nurses and pharmacy personnel from eight hospitals to cyclophosphamide and ifosfamide was determined by quantifying the amount of the drugs handled and by measuring the urinary excretion of the unmetabolised substances. Preparing antineoplastic drugs for intravenous treatment was the major task of all study participants. Twenty four hour urine was collected on days when cyclophosphamide and/or ifosfamide were mixed, on average 3900 mg cyclophosphamide and/or 5900 mg ifosfamide. The analyses were performed by gas chromatography with electron capture, detection limit 2.5 micrograms/24 hour urine. Despite standard safety precautions, including a vertical laminar air flow safety cabinet and gloves, cyclophosphamide was detected in 12 of 31 and ifosfamide in four of 21 urine samples on days when the drugs were handled. Excretion of cyclophosphamide ranged from 3.5 to 38 micrograms/24 h (mean 11.4 micrograms/24 h) urine, ifosfamide from 5 to 12.7 micrograms/24 h (mean 9 micrograms/24 h) urine. Based on an excretion rate of 11.3% unmetabolised cyclophosphamide, the average amount excreted corresponded to an uptake of 101 micrograms cyclophosphamide. For ifosfamide the mean quantity incorporated was 20 micrograms assuming that 45% of the drug was excreted. Pertaining to the doses handled, the uptake of cyclophosphamide and ifosfamide was estimated to be approximately 0.0025% and 0.0004% respectively. Despite time-consuming purification procedures, gas chromatographic analysis is a suitable method for monitoring personnel occupationally exposed to cyclophosphamide and ifosfamide and is a major contribution to the evaluation of potential health risks of exposed personnel.